The extraction of rare earth elements from various resources using the sulfation roastingleaching process - Maluleke, Kgomotso Charlotte (My University, 2022)
Rare Earth elements (REEs) are commonly extracted from mineral concentrates using conventional hydrometallurgical processes such as alkaline and/or acid baking. These processes are known to be highly efficient in extracting the REEs but tend to be highly unselective because they also extract gangue metals such as Fe, Mn and Th. Co-extraction of gangue metals contaminates the product stream and therefore requires multiple purification stages to produce a cleaner sellable product. The non-selectivity of these processes is also associated with high reagent consumptions and the production of large waste streams that are difficult and expensive to discard. The aim of the study was to investigate the technical feasibility of using sulfation roasting and leaching processes for the selective conversion and extraction of LREE (La, Ce, Nd and Pr) from South African REE-bearing resources, i.e. Zandkopsdrift (ZKD) ore and PyEarth ™ slag. This was achieved by conducting fluidized sulfation roasting tests where the effect of operational parameters; temperature, reaction time and stoichiometric ratio of SO2 to O2, on the conversion efficiency of Light REEs (LREEs) in the ZKD ore and the PyEarth ™ slag were investigated. The sulfation roasting and leaching process was proven to be technically feasible for the conversion and extraction of LREEs from both the ZKD ore and PyEarth ™ slag. The study further indicated that the sulfation roasting and leaching process was a function of temperature, time, and gas composition. The highest LREE extractions for the ZKD ore, i.e. 88% La, 87% Pr, 86% Nd, 61% Ce, were obtained for samples roasted at 700°C for 8 hours in an O2-enriched gas atmosphere. Fe was the least extracted metal at all the roasting conditions investigated for the ZKD ore. Sulfation roasting of the PyEarth™ slag was associated with significantly high Fe extractions, highest of 72%, compared to the highest LREE extractions of 24% Nd, 21% Pr, 21% La, and 21% Ce obtained at 700°C for 8 hours in an O2-enriched gas atmosphere. These results indicated that selectivity was attained for the ZKD ore as compared to the PyEarth ™ slag for the conditions that were investigated. It is therefore recommended that more conditions are investigated for the PyEarth ™ slag to make a more accurate conclusion in terms of the applicability and selectivity of the sulfation roasting and leaching process for slag feed materials.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and the Built Environment, School of Chemical & Metallurgical Engineering. University of the Witwatersrand, Johannesburg, 2021